A Textbook by Ioana Visalon, Dedicated to the Organic Approach of Acting (Book Review: Ioana Visalon, Antrenamentul vorbirii scenice / The Voice & Speech Training, Braşov: Transylvania University Publishing House, 2023) - BEŢIU, Mihaela (Studia Universitatis Babeș-Bolyai Dramatica, 2024)
This textbook concentrates a pedagogical experience of over 25 years dedicated to the integration of stage speech in the organic approach of acting, an approach based mainly on the methods created by K.S. Stanislavski, Viola Spolin, and Ion Cojar. The author substantiates her pedagogical approach on the need that the actor’s speaking be the expression of spontaneous, honest reactions to the Magical If. This requires a training that progressively consolidates the use of new speaking skills in the complicated process of rethinking the memorized text and activating the creative imagination. The book is also the first Romanian Voice & Speech textbook that offers a coherent and comprehensive training method structured on the Broadwell model of learning skills (adapted by Carey & Clarck Carey to Voice & Speech practice), it capitalizes on in-depth documentation, not only in the specialized literature of the discipline, but also in fields such as neuroscience or psycholinguistics, and includes no less than 104 exercises, described comprehensibly and in detail, as well as an excellent theoretical apparatus updated and adapted to the needs of student actors.